PART OF TURKISH WORDS FROM THE FIELD OF HYDROGRAPHY - Trifunovska Janikj, Sunchica (International Scientific Journal Vision, 2025)
During its historical development, the Macedonian language, like all other languages, was exposed to influences from other languages. Macedonia was under Turkish rule for five and a half centuries, so we can say that Turkishisms are the most numerous in the Macedonian lexicon in all areas of life. In this paper, we will consider some of the Turkicisms from the field of hydrography that we find in entire regions of the Macedonian dialect area and some that are represented only in the island area. According to the Questionnaire for collecting material for the Macedonian Dialect Atlas, in this paper we will process some of the Turkish lexical units. Based on the dialect material from the Macedonian dialect atlas project at the Macedonian Language Institute „Krste Misirkov“ in Skopje, we will first give a geographical distribution of names. Then we will give a semantic analysis of the Turkish names according to the Interpretive Dictionary of the Macedonian language and finally we will give an etymological analysis.